2020
DOI: 10.1101/2020.06.12.20129650
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Burnout among healthcare professionals during COVID-19 pandemic: a cross-sectional study

Abstract: Background: The unpredictable nature of the new COVID-19 pandemic and the already alarming incidence of healthcare workers being affected can have a significant impact on the psychological well-being of the staff. Objective: To describe the prevalence of burnout among healthcare professionals and the associated factors. Design: Cross-sectional survey. Setting: Eight university affiliated hospitals in the capital city of Tehran, Iran. Participants: All healthcare workers at the study sites who had been taki… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 45 publications
8
65
0
Order By: Relevance
“…Being a 'once-in-a-century pandemic', 29 some of the misgivings affecting HCWs include the fear of contracting a lethal virus and spreading it to the rest of their social network, lack of evidence-based prevention and intervention, lack of essential protective gear and the fact that the pandemic requires protracted shifts with a high volume of patients with different degrees of pathology and severity. [30][31][32][33][34][35][36][37][38][39][40][41][42][43] This would imply that HCWs are now working in a uniquely hazardous situation and are thus vulnerable to stress and distress. In addition to operational stresses, some preliminary studies have suggested that psychosocial dysfunctions are rife among HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…Being a 'once-in-a-century pandemic', 29 some of the misgivings affecting HCWs include the fear of contracting a lethal virus and spreading it to the rest of their social network, lack of evidence-based prevention and intervention, lack of essential protective gear and the fact that the pandemic requires protracted shifts with a high volume of patients with different degrees of pathology and severity. [30][31][32][33][34][35][36][37][38][39][40][41][42][43] This would imply that HCWs are now working in a uniquely hazardous situation and are thus vulnerable to stress and distress. In addition to operational stresses, some preliminary studies have suggested that psychosocial dysfunctions are rife among HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…After the screening of the titles and abstracts, we removed 191 records and we added 4 more records found by the reference lists scanning. Finally, we included 14 studies [27][28][29][30][31][32][33][34][35][36][37][38][39][40] in this systematic review that met our inclusion criteria and among them six studies in the meta-analysis that included the appropriate data.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
“…Main characteristics of the 14 studies included in our systematic review are shown in Table 1. Study population included only nurses in five studies, 27,28,33,36,40 while nine studies [29][30][31][32]34,35,[37][38][39] included HCWs in general. A total of 17,390 nurses were included in this systematic review, while two studies 37,38 did not report the number of nurses.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“… 9 A recent cross-sectional study from Iran reported that 53.0% of HCWs were burned out in the pandemic COVID-19 period. 10 Another review reported higher ranges of burned out among physicians specifically for emotional exhaustion, depersonalization, and low personal accomplishment. 10 , 11 Additionally, social isolation, particularly when staff were exposed to prolonged quarantine, and the fear of infecting their family or having an infected family member were reported as reasons for higher rates of stress related illnesses in HCWs during crisis.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Another review reported higher ranges of burned out among physicians specifically for emotional exhaustion, depersonalization, and low personal accomplishment. 10 , 11 Additionally, social isolation, particularly when staff were exposed to prolonged quarantine, and the fear of infecting their family or having an infected family member were reported as reasons for higher rates of stress related illnesses in HCWs during crisis. 12 Moreover, staff may be worried due to feelings of uncertainties faced with critically ill patients.…”
Section: Introductionmentioning
confidence: 99%